Contribution of Glacier, Snow and Rain Components in Flow Regime Projected with HBV Under AR5 Based Climate Change Scenarios Over Chitral River Basin (Hindukush Ranges, Pakistan) - A, Burhan; Usman, M; Bukhari, S. A. A; Sajjad, H (International Journal of Climate Research, 2020)
Knowledge of projection and attribution of streamflow composition in rain and snow fed glaciated catchments has been of vital significance to a spectrum of stakeholder communities. Accordingly, assessment of contributed share of rain, snow and glacier to downstream flow regime in snowy and glaciated catchment area of Chitral River Basin (CRB) in historical and projected periods was made in this study. HBV-Light hydrological model (hereafter HBV) was used to identify temporal variation and composition of streamflow in response to alterations in hydro-meteorological parameters over the CRB. The HBV was seen to perform fairly well both during calibration (R2=0.91, Reff=0.91) and validation (R2=0.91, Reff=0.81) periods on daily time scale in the CRB. The HBV was thereafter deployed for prediction of streamflow changes and composition in the CRB using Assessment Report 5 (AR5) based projections. Projected patterns indicated significant changes in flows with up to 26.7% increase that were attributed to up to 6.6 °C increase in the temperature under a high end emission scenario over the basin. Whereas a loss in contribution of snow was seen, a simultaneous increase of up to 28% in the contribution of glacier melt with significant density increase is projected for the flow regime under the high end emission scenario. Moreover, the significant increase in glacier melt was found in phase with residence of high temperatures forced with the emission scenarios in the CRB over the projected periods.